Assessing Digital Competence and Its Relationship with the Socioeconomic Level of Chilean University Students - Silva-Quiroz, J (Springer Science and Business Media Deutschland GmbH, 2022)
Digital competence (DC) is one of the key aspects in citizen development in the digital age. The DC is particularly important in forming university students and future teachers. This article presents the main results of a study to evaluate DC and its relationship with the socioeconomic level of first-year students of pedagogy in three Chilean public universities, located in the north, center, and south of the country. A quantitative research methodology was used, with a sample of 817 students, the data were collected through the DIGCOMP-PED evaluation instrument, which evaluates DC development using the DIGCOMP framework. The results were analyzed at the general and socioeconomic level on the variables of the educational establishment where they attended high school and the territorial area of the university they attended. The main results indicate that the level of DC achievement is intermediate, the areas with the highest levels of achievement were “network security” and “online communication and collaboration.” On the other hand, the lowest levels of achievement were reached in the areas “information and digital literacy,” “digital content creation,” and “problem solving.” The level of DC is higher among students of private establishments and those who attend universities located in the central area. © 2022, The Author(s).